Additional compensation for violation of fundamental rights of Article 183 LRJS. Reflections about their aims and their calculation - Crespo Ortiz, David (LABOS Revista de Derecho del Trabajo y Protección Social, 2023)
Article 183 of Law 36/2011; of October 10; regulating social jurisdiction; introduced additional compensation in the Spanish legal system in case of violation of fundamental rights in the social order; not entirely unknown previously; with some nuances in its typicality that raises a series of questions related to the nature of what is being compensated and its determination. Along these lines we analyze the main characteristics with which the jurisprudence endows this compensation; as well as the different elements that are currently used in its calculation.